SIKAP PROFESIONAL GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM - Usman, Usman (Inspiratif Pendidikan, 2023)
In studying the professional attitude of teachers in the perspective of Islamic education, 4 basic questions have been developed, namely: (1) what is the meaning of the professional attitude of teachers; (2) what is the target of the teacher’s professional attitude; (3) how to develop the teacher’s professional attitude; and (4) how is the teacher’s professional attitude in the perspective of Islamic education? To answer this problem, the authors examine it through literature searches, both based on theory, trade regulations, and through studies of the Koran and the Hadith of the Prophet. The results of a literature search found that: (1) the teacher’s professional attitude is an action or activity in the form of a good example in carrying out duties as a teacher who has high knowledge, attitudes, and skills in carrying out basic teacher duties; (2) the teacher’s professional attitude includes: (a) attitude towards students; (b) attitudes towards leaders/leaders; (c) attitudes towards colleagues; (d) attitudes towards professional organizations; (e) attitude towards work; (f) attitudes towards the workplace; and (g) attitudes towards legislation; (3) the development of this professional attitude can be carried out through two stages, namely: pre-service education (pre-service education) and in-service education/in-service training (in-service education/training); and (4) the attitude of professionalism in Islamic education, namely the actions of a teacher who not only teaches but also educates with only scientific and academic qualifications, but more importantly has commendable morals, such as having patience in teaching, conveying what is called for with full honesty , and carry out educational activities with sincerity. It is hoped that this article can provide benefits and insights for readers regarding the professional attitude of teachers in an Islamic perspective and make it a basis for thinking and acting in carrying out the duties of the teaching profession, so that it is not only as giving up duties and obligations, but at the same time as worship on the side of Allah SWT